2018
DOI: 10.1186/s13031-018-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-communicable diseases and access to care among non-camp Syrian refugees in northern Jordan

Abstract: BackgroundTackling the high non-communicable disease (NCD) burden among Syrian refugees poses a challenge to humanitarian actors and host countries. Current response priorities are the identification and integration of key interventions for NCD care into humanitarian programs as well as sustainable financing. To provide evidence for effective NCD intervention planning, we conducted a cross-sectional survey among non-camp Syrian refugees in northern Jordan to investigate the burden and determinants for high NCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
118
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 16 publications
13
118
1
Order By: Relevance
“…Looking at the non-modi able risk factors for NCDs, we found that higher age was associated with higher NCDs prevalence, consistent with previous ndings (45,63). This is further supported by evidence suggesting that susceptibility to NCDs increases with age (71).…”
Section: Prevalence Of Ncdssupporting
confidence: 90%
“…Looking at the non-modi able risk factors for NCDs, we found that higher age was associated with higher NCDs prevalence, consistent with previous ndings (45,63). This is further supported by evidence suggesting that susceptibility to NCDs increases with age (71).…”
Section: Prevalence Of Ncdssupporting
confidence: 90%
“…The daily stressors, financial precarity, the myriad barriers to accessing care experienced by Syrian refugee NCD patients in Jordan and the potentially harmful decisions they make as a result of stretched finances have been well documented in our own and others' studies [43,[55][56][57][58]. The free care provided by MSF goes some way to alleviating the NCD-related financial burden affecting their current cohort.…”
Section: Implications For Integrated Mhpss and Ncd Services In Humanimentioning
confidence: 99%
“…The Middle East and North Africa (MENA) accounts for 6% of the global population but comprises 25% of the 'population of concern' to the UN Refugee Agency (including refugees, internally displaced persons, asylum-seekers and stateless persons). The vast majority of refugees in the MENA region live outside of camp settings in urban and semi-urban environments in Jordan, Lebanon and Turkey [1][2][3]. In addition to large numbers of displaced persons in urban settings, the region is also undergoing an epidemiologic transition towards more noncommunicable diseases (NCDs).…”
Section: Introductionmentioning
confidence: 99%